Emerging molecular predictive and prognostic factors in acute myeloid leukemia. Issue 9 (2nd September 2018) - McCurdy, Shannon R.; Levis, Mark J.
Abstract: Recurrent cytogenetic abnormalities have provided the backbone for prognosticating acute myeloid leukemia and predicting response to consolidative therapies for decades. However, more than 45% of acute myeloid leukemia patients have normal cytogenetics on both karyotype and fluorescence in situ hybridization at diagnosis. Increasingly utilized next-generation sequencing has led to the discovery of numerous recurrent molecular mutations in acute myeloid leukemia, which can currently be identified in 97.3% of patients. Despite the prevalence of dozens of these recurrent lesions, only NMP1, CEBPA, KIT, FLT3-ITD, and TP53 have been incorporated into widely accepted risk-stratification schemas, such as the 2017 National Comprehensive Cancer Network guidelines. Here we review the most frequent molecular genetic abnormalities, their utility in predicting relapse and survival, and their function as markers of minimal residual disease. We also provide a summary of sixteen common recurrent molecular abnormalities about which sufficient data exists (Table 1 ).